From molecular genetics to genomics : the mapping cultures of twentieth-century genetics - Gaudillière, Jean-Paul, 1957-; Rheinberger, Hans-Jörg (Routledge studies in the history of science, technology, and medicine, 2004)
With the rise of genomics, the life sciences have entered a new era. This book provides a comprehensive history of molecular genetics and genomics.- Resumé vydavatel